Effects of training on the heart rate variability of competitive soccer players: A systematic review with meta-analysis - García-Ortega, D.; Granero-Gallegos, A.; Carrasco-Poyatos, M. (International Journal of Sports Science & Coaching, 2023)
Heart rate variability (HRV) has become a popular method for monitoring readiness, recovery, and other training-derived parameters to optimize physical performance. This systematic review aimed to examine the impact of training interventions on HRV fluctuations in competitive soccer players. The EBSCO, Web of Sciences (WOS), and Cochrane databases were used for the search. After identifying 293 studies, 13 were included in a qualitative analysis and 6 in a quantitative analysis. Training had a small and nonsignificant effect on HRV in competitive soccer players (Effect Size (ES) = 0.143, Standard Error (SE) = .108, p = .186, 95% confidence interval (CI) [-0.69, 0.355]). Soccer-focused training resulted in higher HRV scores than combined training (Q(2) = 38.13, p = .05). Higher ES were found for frequency domain parameters (p = .047; d = 0.059), night assessment (p = .016; d = 0.453), and soccer-focused training (p = .006; d = 0.366). HRV was also found to have a greater impact on females (p = .027; d = 0.275) and/or professional soccer players (p = .007; d = 0.302). Soccer training had a minimal and nonsignificant effect on HRV.